Strategi Dalam Peningkatan Mutu Pembelajaran Pendidikan Agama Islam - rohman, fathur (FATAWA: Jurnal Pendidikan Agama Islam, 2021)
Achieving the quality of education is a step that must be done with efforts to improve the professional abilities of teachers. Mainly Islamic religious education teachers. Education has an important role in improving human quality. Therefore, humans are a central force in development, so that the quality and success of the education system can be determined through increasing student achievement. The knowledge gained from the educational process is an important provision for everyone to carry out life. The teacher's efforts in improving student learning are felt to have a very large influence on the behavior of students. To be able to change the behavior of students as expected, it is necessary to have a professional teacher, namely a teacher who is able to use all components of education so that the teaching and learning process runs well. The results of this study describe the process of Islamic religious education teachers' efforts in improving student achievement in Islamic religious education subjects through extra-curricular activities, discussion of questions, improving the quality of Islamic religious teachers (KKG), learning methods. Every activity in an effort to improve learning achievement is always influenced by supporting and inhibiting factors both from within (intrinsic) and from outside (extrinsic). Likewise, in an effort to improve student achievement. There are several supporting and inhibiting factors experienced by Islamic Religious Education teachers.